- Formulasi Sediaan Nanoemulsi Ekstrak Daun Jambu Biji (Psidium Guajava L.) Sebagai Bahan Aktif Pembuatan Serum Antioksidan: Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan - SHAFA, ARIFAH ZHAFIRAH; Noor Fitri (Chemistry Department, Universitas Islam Indonesia, 2023)
This research had been carried out on the formulation of guava leaf extract nanoemulsion as an active ingredient of antioxidant serum. The steps of this research include: (1) extraction by maceration; (2) Characterization and identification of extracts include phytochemical test, DPPH test, shear reagent test, and identification of compounds using LC-MS/MS; (2) formulation of nanoemulsion using Self-Nanoemulsifying Drug Delivery System (SNEDDS) method; (4) Nanoemulsion testing: stability test, antioxidant activity test using DPPH method, and irritation test, (5) nanoemulsion characterization which includes particle size, transmittance, pH, and viscosity. The results showed that: (1) the extract yields of the maceration method were 15,048%; (2) antioxidant compounds in Guava leaf extract were Candidate Mass C35H42O9, Candidate Mass C26H48O15, Candidate Mass C34H40O9, quercetin dan quercetin-3-O-α-L- arabinopyranoside; The IC50 of the macerated extract were 59,771 ± 1,357 ppm; (3) Nanoemulsions were made in 3 formulas (0.5; 1; and 1,5 g) with fixed variables of capryol 90, tween 20, and PEG 400 (1,5; 2,5; and 1); (4) stability test showed that only F1 was stable; the IC50 value of nanoemulsion is 509,039 ppm; and the F1 irritation test showed no erythema and edema; (5) The particle size of F1 was 168,2 nm with a transmittance value of 96,10%, a pH of 5,45, and a viscosity of 73,88 cP. So that the preparation of guava leaf extract nanoemulsion is not recommended as an active ingredient for making antioxidant serum. Keywords : Guava Leaf, Nanoemulsion, Antioxidant, Serum, SNEDDS